Maternal periconceptional folic acid intake and risk of autism spectrum disorders and developmental delay in the CHARGE (CHildhood Autism Risks from Genetics and Environment) case-control study - Schmidt, Rebecca J; Tancredi, Daniel J; Ozonoff, Sally; Hansen, Robin L; Hartiala, Jaana; Allayee, Hooman; Schmidt, Linda C; Tassone, Flora; Hertz-Picciotto, Irva (The American journal of clinical nutrition, 2012)
Periconceptional folate is essential for proper neurodevelopment. Maternal folic acid intake was examined in relation to the risk of autism spectrum disorder (ASD) and developmental delay (DD). Families enrolled in the CHARGE (CHildhood Autism Risks from Genetics and Environment) Study from 2003 to 2009 were included if their child had a diagnosis of ASD (n = 429), DD (n = 130), or typical development (TD; n = 278) confirmed at the University of California Davis Medical Investigation of Neurodevelopmental Disorders Institute by using standardized clinical assessments. Average daily folic acid was quantified for each mother on the basis of dose, brands, and intake frequency of vitamins, supplements, and breakfast cereals reported through structured telephone interviews. Mean (±SEM) folic acid intake was significantly greater for mothers of TD children than for mothers of children with ASD in the first month of pregnancy (P1; 779.0 ± 36.1 and 655.0 ± 28.7 μg, respectively; P < 0.01). A mean daily folic acid intake of ≥600 μg (compared with <600 μg) during P1 was associated with reduced ASD risk (adjusted OR: 0.62; 95% CI: 0.42, 0.92; P = 0.02), and risk estimates decreased with increased folic acid (P-trend = 0.001). The association between folic acid and reduced ASD risk was strongest for mothers and children with MTHFR 677 C>T variant genotypes. A trend toward an association between lower maternal folic acid intake during the 3 mo before pregnancy and DD was observed, but not after adjustment for confounders. Periconceptional folic acid may reduce ASD risk in those with inefficient folate metabolism. The replication of these findings and investigations of mechanisms involved are warranted.